2015
DOI: 10.12688/f1000research.5403.2
|View full text |Cite
|
Sign up to set email alerts
|

Breaking a Guinness World Record on Hand Sanitizing Relay, initiating a call for vital research in overcoming campaign fatigue for hand hygiene

Abstract: Hand hygiene has been shown to be effective in significantly reducing hospital acquired infections for many years. However it is difficult to maintain and enhance compliance with hand hygiene guidelines. In Hong Kong, we previously reported a strategy to counter campaign fatigue from 50%-55% in 2009-11 to 83% in 2012. Here we report a creative activity that we used to sustain and enhance hand hygiene compliance. In May 2014 we broke the first Guinness World Record for a Hand Sanitizing Relay. A total of 277 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The result of the study was consistent with the previous study in which increased awareness among participants was noticed after the world record attempt. In that particular study, the increase in hand hygiene compliance was identified after world record attempt [1]. Similarly, in our study, we found an increased level of awareness among participants about the role of Yoga in Diabetes management which is indicated by the fact that 96% participants acknowledged Yoga as a means of Diabetes management.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The result of the study was consistent with the previous study in which increased awareness among participants was noticed after the world record attempt. In that particular study, the increase in hand hygiene compliance was identified after world record attempt [1]. Similarly, in our study, we found an increased level of awareness among participants about the role of Yoga in Diabetes management which is indicated by the fact that 96% participants acknowledged Yoga as a means of Diabetes management.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, attempts to break world record on International Day of Yoga by organising the Diabetes awareness lesson is a unique method of academic social responsibility. In this present campaign a total of 498 individuals participated which is significantly higher than the previous Guinness record attempt on hand hygiene in which total 227 individuals had participated [1]. The sex ratio of the participants was almost equal but a number of participants from A AN NN NA AL LS S RES ARTICLE the urban area were more when compared to rural which indicates the need for an awareness campaign in rural localities of the country.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations